IL-6 Quotient (The Ratio of Cerebrospinal Fluid IL-6 to Serum IL-6) as a Biomarker of an Unruptured Intracranial Aneurysm - Kamińska J; Dymicka-Piekarska V; Chrzanowski R; Sawicki K; Milewska AJ; Zińczuk J; Tylicka M; Jadeszko M; Mariak Z; Kratz EM; Matowicka-Karna J; Kornhuber J; et al. (Dove Medical Press, 2021)
Joanna Kamińska,1 Violetta Dymicka-Piekarska,1 Robert Chrzanowski,2 Karol Sawicki,2 Anna J Milewska,3 Justyna Zińczuk,1 Marzena Tylicka,4 Marek Jadeszko,2 Zenon Mariak,2 Ewa M Kratz,5 Joanna Matowicka-Karna,1 Johannes Kornhuber,6 Piotr Lewczuk,6,7 Olga M Koper-Lenkiewicz1 1Department of Clinical Laboratory Diagnostics, Medical University of Białystok, Białystok, 15-269, Poland; 2Department of Neurosurgery, Clinical Hospital of the Medical University of Białystok, Białystok, 15-276, Poland; 3Department of Statistics and Medical Informatics, Medical University of Białystok, Białystok, 15-295, Poland; 4Department of Biophysics, Medical University of Białystok, Białystok, 15-089, Poland; 5Department of Laboratory Diagnostics, Division of Laboratory Diagnostics, Faculty of Pharmacy, Wrocław Medical University, Wrocław, 50-556, Poland; 6Department of Psychiatry and Psychotherapy, Friedrich-Alexander-Universität Erlangen-Nürnberg, Universitätsklinikum Erlangen, Erlangen, 91054, Germany; 7Department of Neurodegeneration Diagnostics, Medical University of Białystok, Białystok, 15-269, PolandCorrespondence: Joanna Kamińska; Olga M Koper-LenkiewiczDepartment of Clinical Laboratory Diagnostics, Medical University of Bialystok, Waszyngtona 15A St., Białystok, 15-269, PolandTel/Fax +48 85 7468584Email joanna.kaminska@umb.edu.pl; o.koper@wp.plBackground: Studies conducted so far have focused mainly on the assessment of IL-6 levels in patients with ruptured brain aneurysms. Carrying out detailed studies in patients with un-ruptured brain aneurysms (UIA) would be extremely important, as it would answer the question of whether IL-6 plays also a role in primary aneurysm formation and growth.Methods: IL-6, S100, NSE, and albumin concentrations in 67 UIA patients and 17 individuals without vascular lesions in the brain were tested using in vitro diagnostic immunoassays according to the manufacturers' instructions. IL-6 Quotient was calculated by dividing cerebrospinal fluid (CSF) IL-6 by serum IL-6.Results: We showed that IL-6 Quotient was significantly higher in UIA patients (1.78) compared to the control group (0.87; p< 0.001). Multivariate logistic regression analysis demonstrated that a growth in IL-6 Quotient increases the probability of UIA diagnosis. In UIA patients CSF IL-6 concentration was significantly higher (4.55 pg/ml) compared to the serum concentration (2.39 pg/ml; p< 0.001). In both the study and control group, the blood-brain barrier was intact, thus the CSF-blood gradient of the IL-6 concentration in UIA patients was likely to be the expression of local synthesis of the cytokine within the central nervous system. Patients with multiple brain aneurysms had significantly higher CSF IL-6 levels (5.08 pg/ml) compared to individuals with a single aneurysm (4.14 pg/ml; p=0.0227).Conclusion: This totality of the may suggest IL-6 as a biomarker for UIA formation; however, further studies are needed to unequivocally confirm clinical application of IL-6 concentration evaluation.Keywords: cerebrospinal fluid, CSF, interleukin 6, IL-6, unruptured intracranial aneurysm, UIA, IL-6 Quotient